How Consumer Decision Making Process Differ From Youngster to Older Consumer Generation - Yap, Chloe Wai San; Yazdanifard, Rashad (Journal of Research in Marketing (ISSN: 2292-9355), 2014)
The vital moment for most, if not all marketers, is when the consumers decide on whether or not the particular product or service would be paid for. That indicates whether the intended marketing strategies have been wise, insightful, and effective, or otherwise poorly done and have lost the target. By understanding how consumers make purchase decisions is important to every marketer in order to develop a marketing strategy to meet their targeted consumer’s needs, wants, and desires. This research focuses to review how consumer decision making differ from younger and older consumer generations.